A biomimetic nanoreactor for synergistic chemiexcited photodynamic therapy and starvation therapy against tumor metastasis. Issue 1 (December 2018) - Yu, Zhengze; Zhou, Ping; Pan, Wei; Li, Na; Tang, Bo
Abstract Photodynamic therapy (PDT) is ineffective against deeply seated metastatic tumors due to poor penetration of the excitation light. Herein, we developed a biomimetic nanoreactor (bio-NR) to achieve synergistic chemiexcited photodynamic-starvation therapy against tumor metastasis. Photosensitizers on the hollow mesoporous silica nanoparticles (HMSNs) are excited by chemical energy in situ of the deep metastatic tumor to generate singlet oxygen (1 O2 ) for PDT, and glucose oxidase (GOx) catalyzes glucose into hydrogen peroxide (H2 O2 ). Remarkably, this process not only blocks the nutrient supply for starvation therapy but also provides H2 O2 to synergistically enhance PDT. Cancer cell membrane coating endows the nanoparticle with biological properties of homologous adhesion and immune escape. Thus, bio-NRs can effectively convert the glucose into1 O2 in metastatic tumors. The excellent therapeutic effects of bio-NRs in vitro and in vivo indicate their great potential for cancer metastasis therapy. Photodynamic therapy is usually ineffective against deeply seated metastatic tumors due to poor penetration of the excitation light. Here, the authors design a biomimetic nanoreactor which can convert nutriment glucose into toxic singlet oxygen via chemiluminescence resonance energy transfer with no light excitation and demonstrate its high efficacy in a mouse lung metastatic model.